2014
DOI: 10.1093/icesjms/fsu198
|View full text |Cite
|
Sign up to set email alerts
|

Looking in the rear-view mirror: bias and retrospective patterns in integrated, age-structured stock assessment models

Abstract: Retrospective patterns are systematic changes in estimates of population size, or other assessment model-derived quantities, that occur as additional years of data are added to, or removed from, a stock assessment. These patterns are an insidious problem, and can lead to severe errors when providing management advice. Here, we use a simulation framework to show that temporal changes in selectivity, natural mortality, and growth can induce retrospective patterns in integrated, age-structured models. We explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 14 publications
1
58
0
Order By: Relevance
“…ICES (2007) conducted such simulation testing and found that the cause of a retrospective pattern could not be identified based on any of the explored diagnostics. This result was recently confirmed by Hurtado-Ferro et al (2015) using a more extensive factorial design. Preliminary management strategy evaluations demonstrated that fixing the retrospective pattern, even using the wrong fix relative to the true cause, produced better performing management advice than ignoring the retrospective pattern (ICES 2008).…”
Section: Introductionsupporting
confidence: 55%
“…ICES (2007) conducted such simulation testing and found that the cause of a retrospective pattern could not be identified based on any of the explored diagnostics. This result was recently confirmed by Hurtado-Ferro et al (2015) using a more extensive factorial design. Preliminary management strategy evaluations demonstrated that fixing the retrospective pattern, even using the wrong fix relative to the true cause, produced better performing management advice than ignoring the retrospective pattern (ICES 2008).…”
Section: Introductionsupporting
confidence: 55%
“…Though not addressed in this analysis, bias in biomass estimates is also an important consideration for managers. Retrospective bias, which might arise from unanticipated changes in growth or mortality (Hurtado‐Ferro et al., ), could compound the negative impacts of delayed detection and should be considered when testing potential control rules for specific populations. Additionally, although we assume in this analysis that reference points are known by the managers, over‐ or underestimation of those reference points can lead to changes in control rule performance.…”
Section: Discussionmentioning
confidence: 99%
“…Information on biology and population dynamics is essential for monitoring the rational exploitation and management of the stock (Mehanna 2007). Recent studies (detailed in Deroba et al 2015;Hurtado-Ferro et al 2015;Johnson et al 2015;Ono et al 2015) suggested that there are many challenges still to be resolved when applying multiple models to a single stock.…”
Section: Introductionmentioning
confidence: 99%